Heat‐induced structural changes in fish muscle collagen related to texture development in fish balls: Using eel ball as a study model. Issue 2 (19th July 2021) - Wang, Yafei; Wang, Xufeng; Lin, Chuntong; Yu, Mengqin; Chen, Shanshan; Guo, Jingke; Rao, Pingfan; Miao, Song; Liu, Shutao
Abstract: In order to elucidate the substantial effect and underlying mechanism of endogenous collagen on the texture development of fish balls, the structural and gelling properties of eel muscle collagen (EMC) under different heat treatments, as well as their effects on texture of eel ball, were investigated. EMC resulted in significant improvement of eel ball texture via gelling ability, filler effect, and interaction with starch. Under mild heating below 90°C for 30 min, the structural and physicochemical changes of EMC varied gradually, resulting in improved storage modulus of starch‐containing myofibrillar gel, a mimic of eel ball. However, overheating (100°C, 30 min) induced EMC degradation and significantly decreased the gel formation and the improvements in textural properties. Supplementation of EMC to eel balls significantly improved its gel strength, springiness, cohesiveness, and chewiness, as well as uniformity and tightness of the microstructure. These results suggest the texture development of eel ball can be regulated by heat‐induced structural changes, as well as structure–function relationship of collagen, compared with previous studies on myofibrillar proteins and exogenous gelatin; and they may provide texture‐related insights to the quality control of fish balls and diverse heat‐treated products of surimi containing collagen. Abstract : 1. Heat‐induced structure changes of eel muscle collagen (EMC) in eel ball were verified and were closely related to the texture of eel ball. 2. Mild heating of EMC improved the textural profile of mimic eel ball; overheating induced EMC degradation and decreased the gel forming ability. 3. Overheating‐induced EMC degradation decreased textural improvement in eel ball.